Analysis of Student Suicide Cases in Electronic Media: Perspectives and the Role of Islamic Education - Jihad, Fauzan Addinul; Azani, Mohammad Zakki (Universitas Muhammadiyah Surakarta, 2023)
This study focuses on the spike in suicide rates among students highlighted in electronic media. The goal is to identify the problems faced by students as well as how these problems contribute to the emergence of suicidal ideas as an escape option. With a qualitative method through literature study, this research explores data from various sources such as journals, articles, and related papers. The sociological approach is used to emphasize the need to seriously handle the problem of suicide among students. Furthermore, this study emphasizes the importance of spiritual aspects in social contexts as the key to suicide prevention. The concept of science is based on Islam, Faith, and Ihsan as a prevention strategy for suicide and depression. These efforts are expected to strengthen social integration, improve mental well-being, and overcome suicide cases, so it becomes a very crucial discussion in this framework.